Mass, full and half sib-selection for genetic improvement in fennel (Foeniculum vulgare Mill.) - Sastry, V V Singh, E V Divakara (Journal of Spices and Aromatic Crops, 2003)
A study was conducted to estimate genetic variances and heritability for yield and yield attributes in fennel UF-143 population using North Carolina Design-I. The dominance component was high for days to 50% flowering, branches per plant, umbels per plant, seeds per umbel, seed yield, harvest index and test weight. Preponderance of additive gene action was observed for plant height, umbellets per umbel and biological yield. The heritability in narrow sense was high for biological yield. Among the various methods for which theoretical responses were calculated, mass selection appeared suitable for the improvement of biological yield, harvest index, test weight, seed yield, umbellets per umbet umbels per plant and branches per plant.